A Systematic Literature Review on Sustainability Awareness: How Does It Contribute to Science Education - Maryanti, Sri; Riandi; Sopandi, Wahyu; Rusyati, Lilit (UIN Sunan Gunung Djati Bandung, 2025)
Objective : Sustainability awareness has become an important topic in education, particularly in biology, where understanding ecosystems and human interactions with the environment is a major focus. This article reviews existing literature to explore how sustainability awareness contributes to biology education. This review aims to identify and analyze literature that addresses the role of sustainability awareness in improving students' understanding of biology concepts and promoting sustainable practices. Methods: Data was collected by searching literature sources for articles using specific criteria. Fifteen articles were synthesized in greater depth to answer the research questions. The results of this study state that the methodology and assessment tools influence the form and purpose of the research data to be achieved both qualitatively and quantitatively. In addition, the concepts in biological education are closely related to the environment so it is very important to ensure that future generations have a strong understanding of sustainability issues and can contribute to sustainable development in society with sustainability awareness to be able to achieve sustainable goals. Novelty: In increasing the contribution of sustainable development, it is necessary to facilitate interesting teaching materials and learning strategies in order to implement ESD. The learning process has an important role in supporting the improvement of a strong understanding of sustainability awareness. Can be done with a mixed method approach to make the research more comprehensive.